Effectiveness of Sintetic Retardan on Growth and Display Period of Sunflower (Hellianthus annus L.). - Imam Suhadi, Nurhidayati, Bona AS . (Universitas 17 Agustus 1945 Samarinda, 2017)
The aims of research are to know the effects of Sintetic Retardanon the growth of sunflower and determine the effectivenessof Sintetic Retardan on the growthand display period of sunflower. This research was conducted in experiment land of STIPER Kutai Timur from November 2016 to March 2017, used a Completely Randomize Design with 4 treatments and 6 replications. The material of Sintetic Retardan is paclobutrazol. The treatment consisted of (P0)0 ppm, (P1) 40 ppm, (P2) 50 ppm, (P3) 60 ppm. The results showed that paclobutrazol gave significant effect to the growth of sunflower on parameter hight of plant and diameter of stem but not significant on number of leaves. Concentrate 50 ppm of paclobutrazol showed more effectiveness than others on the growth and the display period.